Reliability study of diesel engine operating with biodiesel - Muhamad Harif, Ghani (2010)
The use of alternative fuels issues: reducing the reliance on unstable supply of oil, reduce harmful emissions, and using renewable energy sources. This thesis focuses on the comparison of the four-engine reliability cylinder turbocharged diesel engine operating on diesel fuel and biodiesel. Steady-state tests conducted for the experiment to determine how the input energy adapted form of fuel down the machine. Over energy measured for the loss of engine coolant and exhaust, power output is used, as and light and untold losses. Results showed that the energy input of biodiesel distributed 37.4%, 31.1% and 29.6% into the main area air, exhaust, and power output, respectively. Similarly, to include energy distributed diesel 37.5%, 31.4% and 29.2% of the main areas of air, exhaust pipe, and output power, respectively. It is concluded from an uncertainty Analysis that there was no statistically significant difference in the results. Future improvements to obtain distinguished results are described.